SISTEM PENGAJUAN DAFTAR USUL PENETAPAN ANGKA KREDIT (DUPAK) GURU DAN PENGAWAS KEMENAG PROV. JAMBI GOLONGAN IV/A KE IV/b dI MASA PANDEMI COVID 19 - elfandi putra (Jurnal Bina Ilmu Cendekia, 2021)
Abstract Teachers and Supervisors with the status of ASN have the right guaranteed by the Law to propose promotions in each period. Teachers and supervisors are declared to be promoted to a higher level if the person concerned has a Credit List Proposal List (DUPAK) value reaching the determined cumulative Credit Score (AKK). Besides AKK, Performance Assessment (PK) and Scientific Publication (PI) assessment must also be fulfilled. The assessment output in the form of Teacher and Supervisor Credit Score (PAK) is determined based on the total value of the calculation of physical evidence contained in the Proposed Credit Determination List (DUPAK). The DUPAK assessment process will be assessed and evaluated by an nationally certified assessor team. Over the past years, precisely before the DUPAK proposal for the October 2020 period, proposing and calculating credit numbers in DUPAK still used conventional methods (by paper). These conventional methods certainly require a lot of paper, including binding, and sending DUPAK so that it consumes a lot of time and money. In addition to the process of preparing and sending DUPAK, the verification and assessment process by the assessment team was also forced to be carried out manually as well, including an assessment team meeting to determine the results of the forced evaluation must also be carried out face-to-face. Proposal and evaluation of DUPAK in conventional ways is certainly no longer effective and efficient in the 4.0 era as it is today, especially since the atmosphere is still in the 19th Pandemic era. The government banned activities and activities that gathered large numbers of people during the 19th pandemic. Therefore, to overcome this problem the government, in this case the Indonesian Ministry of Religion through the Director General of Islamic Education issued a regulation contained in the Secretariat General Letter of the Ministry of Religion of the Republic of Indonesia Number B-16308 / B.II / 4 / Kp.01.2 / 05/2020 May 6 2020, the contents of which are dated May 12, which requires DUPAK proposers to make the online submission process. The Ministry of Religion's Civil Service Bureau has developed a method and system for proposing DUPAK teachers and supervisors online, so that the process of proposing and calculating credit numbers is fast and accurate. This new system is built based on online applications, in which there are features that contain elements of activities whose credit numbers will be assessed. Each teacher and supervisor who proposes the rank registers and has their own account. Login through the account that has been made is used by the proposer for data entry required.According to the authors, procedurally and formal legality, the old system and the new system are not much different. But in terms of work effectiveness, the new system is far more effective than conventional methods (by paper). the fundamental difference also lies in the function of online application-based computer technology in the file upload process, so as to shorten the DUPAK submission and assessment process. This research will describe the data and facts arising from an act of using an online application system. The online application in this action research is Simpeg-5 released by the Republic of Indonesia Civil Service Bureau for proposing DUPAK with rank IV / a to IV / b in the period of October 2020.